The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18203/2349-2902.isj20195376
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of laparoscopic assisted versus open complete mesocolic excision for right sided colon cancer

Abstract: Background: Complete mesocolic excision (CME) as a standard surgery for left sided colon cancer is proven however there is a great debate and deal of discussion if the extra effort needed for it in right sided colon cancer worth the gain that is achieved. We aimed in our study to assess the outcome of CME with central vascular ligation for treatment of right sided colon cancer performed either laparoscopic (lap.) assisted or by open technique.Methods: This was a prospective randomized study on sixty patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…After screening of titles and abstracts, 36 studies were analysed in full text, with 12 studies excluded as reported in SDC1, leaving 23 studies matching the inclusion criteria for meta-analysis [ 13 – 47 ], one PhD thesis by El Nakeeb (not published) [ 13 ]. Of these, two references [ 15 , 16 ] report the same data as well as the PhD thesis [ 13 ]. In addition, we found one ongoing study (registered in ClinicalTrials.gov as NCT03826446) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After screening of titles and abstracts, 36 studies were analysed in full text, with 12 studies excluded as reported in SDC1, leaving 23 studies matching the inclusion criteria for meta-analysis [ 13 – 47 ], one PhD thesis by El Nakeeb (not published) [ 13 ]. Of these, two references [ 15 , 16 ] report the same data as well as the PhD thesis [ 13 ]. In addition, we found one ongoing study (registered in ClinicalTrials.gov as NCT03826446) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, the 21 studies included provided data on 5038 patients (Table 1 ). The included studies were published between 2010 and 2020, with participants enrolled between 2000 [ 19 , 34 ] and 2019 [ 13 , 15 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations